2016
DOI: 10.1016/j.jgr.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of joboksansam, Korean wild ginseng germinated from bird feces

Abstract: BackgroundJoboksansam, Korean bird wild ginseng, is an artificially cultivated wild ginseng germinated from bird feces. Although numerous pharmacologic activities of wild ginsengs have been reported, the beneficial effect of joboksansam in cancer has not been elucidated. In this study, we investigated the in vivo and in vitro anticancer activities of joboksansam powder.MethodsTo evaluate the in vivo anticancer activity of joboksansam, we established a xenograft mouse model bearing RMA cell-derived cancer. Dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Various wild, cultivated, and processed forms of ginseng have been reported to have anticancer activity in vivo against hepatocellular carcinoma, Lewis lung carcinoma (LLC-1), and SW480 human colon cancer cells [27] , [28] , [29] , [30] , [31] . In addition, we have demonstrated that wild ginseng-derived root powder displayed clear antileukemia activity [7] . Therefore, the present and previous data strongly suggest that ginseng could be a useful herbal medicine for the prevention and treatment of various types of cancers including leukemia, colon cancer, and hepatoma.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Various wild, cultivated, and processed forms of ginseng have been reported to have anticancer activity in vivo against hepatocellular carcinoma, Lewis lung carcinoma (LLC-1), and SW480 human colon cancer cells [27] , [28] , [29] , [30] , [31] . In addition, we have demonstrated that wild ginseng-derived root powder displayed clear antileukemia activity [7] . Therefore, the present and previous data strongly suggest that ginseng could be a useful herbal medicine for the prevention and treatment of various types of cancers including leukemia, colon cancer, and hepatoma.…”
Section: Resultsmentioning
confidence: 88%
“…Of these, the anticancer activity of KRG is one of the best-studied areas of ginseng research. To date, anticancer and antitumor activities of KRG water extract (KRG-WE), fine black ginseng, ginseng berry extract, wild ginseng, and their individual saponins have been observed in colon, prostate, liver, pancreas, brain, and stomach cancer cells [3] , [4] , [5] , [6] , [7] . Apoptotic activities of ginseng-derived extracts, G-Rg5, G-Rh1, G-Rh2, and G-Rg3, associated with increased levels of caspase 9 and 3 activities have been demonstrated [3] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…RAW264.7 cells were treated with Pg-C-EE. HEK293 cells were independently transfected with each gene ( AKT1-HA , AKT2-HA , or HA ) for 24 h and treated with Pg-C-EE for 24 h. Total lysates and nuclear extracts were prepared as described previously [42] . Immunoblotting of phosphorylated or total levels of transcription factor (p65 and p50), IκBα, IKKα/β, AKT, and p85/PI3K (phosphoinositide 3-kinase) was performed as described previously [42] .…”
Section: Methodsmentioning
confidence: 99%
“… 1988 ; Park, Kang, et al. 2016 ). Briefly, 10 µL of MTT solution (10 mg/mL in phosphate-buffered saline, pH 7.4) was added to the cell culture media, and cells were incubated for 4 h and 15% sodium dodecyl sulphate was added to each well to solubilize the formazan.…”
Section: Preparation Of Peritoneal Macrophagesmentioning
confidence: 99%